Analysis of GNSS station dynamic motion using the multipath effect: analytical, experimental approach and application - Peppa, Ioulia Petroula (2020)
The multipath effect in GNSS measurements remains one of the dominant error sources in GNSS monitoring applications. The site-dependent, fast-changing characteristics of multipath render it difficult to model or predict, introducing errors in GNSS measurements. Current techniques to mitigate the impact of multipath effect focus mainly on repeating GNSS measurements to detect multipath-induced patterns or integrating GNSS with other sensors. However, the multipath effect is used to identify potential changes in the environment in geoscience applications, such as detecting vegetation growth, snow and tidal changes. These applications are based on the concept that for static GNSS antenna, variations in the Signal-to-Noise Ratio (SNR) measurements, induced by the multipath effect during the satellite orbit, express changes in the multipath geometry attributed to different factors (vegetation, tides, snow). In this research, we develop the same concept for an oscillating GNSS antenna focusing on the changes in the multipath geometry caused by the antenna rather than the satellite motion. We investigate the potential of modelling the SNR data of satellite signals and estimating reflection parameters (reflection intensity, antenna-reflector distance, reflector’s tilt) and the motion characteristics (amplitude, frequency and phase of motion). The theoretical SNR models were investigated, and a sensitivity analysis was performed to identify the impact of each parameter on the resulting SNR pattern characteristics. Simulated data then verified the analysis. The models developed in this research were tested in practical trials at the rooftop of the Nottingham Geospatial Institute. The trials allowed the assessment of the phenomenon under real conditions and the role of the hardware (i.e., antenna, receiver) to the overall performance. Finally, in the structural monitoring test, it was shown that there seems to be a benefit from the use of the SNR for the augmentation of the GNSS accuracy.